Diversity, types of diet of bats and their response to Cloud Forest edges, Veracruz, Mexico - Cerón-Hernández, Jacob Arturo; Serna-Lagunes, Ricardo; Torres-Cantú, Gerardo Benjamín; Llarena-Hernández, Régulo Carlos; Mora-Collado, Norma; García-Martínez, Miguel Ángel (Ecosistemas y Recursos Agropecuarios, 2022)
Changes in the richness, abundance and composition of trophic guilds of the bat community are a response to the impact of habitat fragmentation and disturbance; its evaluation is necessary to understand the local adaptation or extinction of bats due to changes in the structure of the original mountain mesophilic forest (BMM) landscape. The objective of the study was to evaluate the richness, abundance, trophic guilds and the response to fragmentation of a bat community in BMM fragments with different degrees of disturbance. During a seven-month monitoring period, fog nets were used to capture bats, placed in four sampling units (MU) with different disturbance conditions; the diversity of bats was described based on the effective number of species and their respective comparisons between MUs. Bats were also classified at the species level, by trophic guild and by their response to the disturbance condition in each MU. 561 individuals of 26 species of bats were recorded, which did not show differences in the effective number of species per MU. The fruit guild was represented by 38% of the bat species and 50% of the registered species had a vulnerable response to the disturbance condition. The observed diversity of bats is a bioindicator that despite the fragmentation and disturbance of BMM, the species have adapted to current landscape conditions.